Supporting mental health during the pandemic: the elements of mattering in expressive writing - Jia Yi Khor; Shakti Velan Raja Kumar; Wen Yu Cai; Chen Sung Wong; Kususanto Ditto Prihadi (International Journal of Public Health Science (IJPHS), 2022)
Previous studies indicated that the sense of mattering played signifant protective role for mental health amidst the pandemic. This current study aims to explore whether elements of mattering in people’s mind are expressed through expressive writing during the hardships such as pandemic situation. Ten young adults who were not diagnosed with any mental health issue were recruited in to take part in an online experiment over a period of four weeks, where they were instructed to expressively write their weekly positive experiences. Thematic analysis suggested that the content of their writings were consistent to the constructs of interpersonal mattering, such as attention, importance and ego extension, as well as the absence of individuality and noted absence. These findings indicated that elements of mattering were embedded in the positive thoughts of our participants, and were expressed through their writings. Further studies are suggested in order to inestigate the effectiveness of expressive writing to improve the sense of mattering to prevent mental health issues during the pandemic.